Controversy Over Sunrang: Analyzing Post-Divorce Ownership in the Context of Makassar Custom and Islamic Law - Abdillah; Sharaf, Salih Yousif; Halim, Annisa Dwi Fadillah (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aimed to analyze the use of sunrang after divorce in Maradekaya Village, Bajeng District, Gowa Regency, from the perspective of Islamic law. The study explored sunrang, often considered similar to mahar (dowry), and the perspective within the context of Bugis-Makassar local culture, where customary law interacts with Islamic legal principles. A descriptive-qualitative design was adopted with a socio-legal method, then primary data was collected through interviews and direct observation. Meanwhile, secondary data was collected from literature and document studies. Data analysis was carried out descriptively and juridically to identify key patterns and themes related to the use of sunrang. The result showed that although sunrang is often treated similarly to mahar in Makassar customs in Maradekaya Village, Bajeng District, Gowa Regency, ownership and return of sunrang after divorce were more influenced by customary law. This result showed that the Makassar community tended to uphold local traditions, suggesting that sunrang remains the property of the wife, despite discrepancies with the stricter principles of Islamic law. This study contributes new insights by combining Islamic and customary law perspectives in analyzing the use of sunrang post-divorce. There was also an understanding of how these two legal systems can influence each other within a strong local cultural context. The implications are significant for the development of clearer legal guidelines regarding ownership of sunrang in both Islamic and customary law. Furthermore, this study showed the need for a more holistic method of resolving sunrang disputes, accommodating both customary norms and Islamic legal principles to maintain social cohesion in the indigenous community of Makassar.